Longitudinal cohort study investigating neurodevelopmental and socioemotional outcomes in school-entry aged children after open heart surgery in Australia and New Zealand: the NITRIC follow-up study protocol - Peter J Anderson; Simon Erickson; Luregn J Schlapbach; Marino Festa; Nadia Badawi; Thomas L Gentles; John Beca; Warwick Butt; Claire Sherring; David Andrews; Natalie A Pride; Samudragupta Bora; et al. (BMJ Open)
Introduction Despite growing awareness of neurodevelopmental impairments in children with congenital heart disease (CHD), there is a lack of large, longitudinal, population-based cohorts. Little is known about the contemporary neurodevelopmental profile and the emergence of specific impairments in children with CHD entering school. The performance of standardised screening tools to predict neurodevelopmental outcomes at school age in this high-risk population remains poorly understood. The NITric oxide during cardiopulmonary bypass to improve Recovery in Infants with Congenital heart defects (NITRIC) trial randomised 1371 children <2 years of age, investigating the effect of gaseous nitric oxide applied into the cardiopulmonary bypass oxygenator during heart surgery. The NITRIC follow-up study will follow this cohort annually until 5 years of age to assess outcomes related to cognition and socioemotional behaviour at school entry, identify risk factors for adverse outcomes and evaluate the performance of screening tools.Methods and analysis Approximately 1150 children from the NITRIC trial across five sites in Australia and New Zealand will be eligible. Follow-up assessments will occur in two stages: (1) annual online screening of global neurodevelopment, socioemotional and executive functioning, health-related quality of life and parenting stress at ages 2–5 years; and (2) face-to-face assessment at age 5 years assessing intellectual ability, attention, memory and processing speed; fine motor skills; language and communication; and socioemotional outcomes. Cognitive and socioemotional outcomes and trajectories of neurodevelopment will be described and demographic, clinical, genetic and environmental predictors of these outcomes will be explored.Ethics and dissemination Ethical approval has been obtained from the Children’s Health Queensland (HREC/20/QCHQ/70626) and New Zealand Health and Disability (21/NTA/83) Research Ethics Committees. The findings will inform the development of clinical decision tools and improve preventative and intervention strategies in children with CHD. Dissemination of the outcomes of the study is expected via publications in peer-reviewed journals, presentation at conferences, via social media, podcast presentations and medical education resources, and through CHD family partners.Trial registration number The trial was prospectively registered with the Australian New Zealand Clinical Trials Registry as ‘Gene Expression to Predict Long-Term Neurodevelopmental Outcome in Infants from the NITric oxide during cardiopulmonary bypass to improve Recovery in Infants with Congenital heart defects (NITRIC) Study – A Multicentre Prospective Trial’. Trial registration: ACTRN12621000904875.